2006
DOI: 10.1007/s00424-006-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of six Kir6.2 (KCNJ11) mutations causing neonatal diabetes

Abstract: ATP-sensitive potassium (K ATP ) channels, composed of pore-forming Kir6.2 and regulatory sulphonylurea receptor (SUR) subunits, play an essential role in insulin secretion from pancreatic beta cells. Binding of ATP to Kir6.2 inhibits, whereas interaction of Mg-nucleotides with SUR, activates the channel. Heterozygous activating mutations in Kir6.2 (KCNJ11) are a common cause of neonatal diabetes (ND). We assessed the functional effects of six novel Kir6.2 mutations associated with ND: H46Y, N48D, E227K, E229K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 47 publications
4
54
2
Order By: Relevance
“…Although for the R301G, R301H, and R301P, channel expression defect is likely the predominant factor underlying loss of channel function, for the R301C mutation channel inactivation likely plays a significant role in causing ␤-cell defect. Curiously, Girard et al (38) recently reported identification of a Kir6.2 mutation E229K in transient neonatal diabetes. Glu-229 forms an intersubunit ion pair with Arg-314, and disruption of this ion pair with the E229R mutation induces rapid current decay or inactivation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although for the R301G, R301H, and R301P, channel expression defect is likely the predominant factor underlying loss of channel function, for the R301C mutation channel inactivation likely plays a significant role in causing ␤-cell defect. Curiously, Girard et al (38) recently reported identification of a Kir6.2 mutation E229K in transient neonatal diabetes. Glu-229 forms an intersubunit ion pair with Arg-314, and disruption of this ion pair with the E229R mutation induces rapid current decay or inactivation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this shift in ATP sensitivity appears to be much greater for mutant channels with gain-of function mutations in Kir6.2 than that of the wild-type channel (Fig. 6) [51][52][53][54][55][56]. Thus it seems that in addition to reduction of the inhibitory effect of ATP, gain-offunction mutations in Kir6.2 can also somehow enhance the activatory effect of Mg-nucleotides.…”
Section: Molecular Basis Of Reduced Atp Sensitivitymentioning
confidence: 96%
“…As a result, channels with gating mutations have increased Po values compared to that of the wild type channel (Fig. 5B) [51,52,54,56,57]. Because the affinity of ATP for the channel open state is smaller than for the closed state, channels are less inhibited by ATP in these mutations.…”
Section: Molecular Basis Of Reduced Atp Sensitivitymentioning
confidence: 97%
See 2 more Smart Citations